Geodiversity and geoconservation in territorial dynamics: The example of the Chapada Diamantina - Giudice, Dante Severo (Seven Editora, 2023)
Chapada Diamantina is located in the central part of the state of Bahia. Its occupation process is closely associated with the Geodiversity, which is the natural variety that exists in the earth's surface, comprising geological and geomorphological aspects that enable and support sustainable development. This development of the region was associated with two cycles, the first of mineral exploration, and later, years later, in 1980, a second, enjoying the sightseeing possibilities, based on the roughness left by the first cycle, but also in scenic beauty as a result of morphological modeling, through the action of weathering (wind and rain). The first cycle promoted the rise of cities and towns, as the abandoned Prospectors’ Village in Igatu. The second cycle uses the caves, ponds, wells and waterfalls. All these attractions are geosites that must be preserved. Thus arises the need for geoconservation, effected through the establishment of conservation units (UC). Thus, the territorial dynamics in the Chapada Diamantina had geodiversity as a driver, but geoconservation is essential to maintain this momentum, because if the attractions are destroyed, this dynamic will collapse. DOI:https://doi.org/10.56238/alookdevelopv1-074